L’exercice du métier de sociologue : réflexion autour de quelques hiatus à la pratique de la sociologie en Afrique - Joseph-Marie Zambo Belinga (Sociologies)
It has never been easy to be a sociologist, given the singular nature of the object of study in one’s scientific field and the many epistemological obstacles to understanding that field. However, it is not the obstacles to the practice of sociology already identified that we propose to revisit in this reflection, but others that the practice of this discipline reveals in the African field. If we look at the margin of initiative that African sociologists allow themselves in the choice of issues on which they work, we find that it is very limited and produces an extroverted sociology. However, a ground-level observation of African societies reveals sites and other objects of sociological investigation rooted in social processes at the heart of systems of domination, exploitation, marginalisation and enslavement of disadvantaged social strata by the dominant ones, which are the primary challenge to the sagacity of sociologists. After reviewing some of these obstacles and showing how they delay the emergence of a sociology focused on the realities that lie at the heart of African societies, this paper will explore ways of changing the paradigm.